LRRK2 and α-Synuclein: Distinct or Synergistic Players in Parkinson’s Disease? - O’Hara, Darren M.; Pawar, Grishma; Kalia, Suneil K.; Kalia, Lorraine V. (Frontiers in Neuroscience, 2020)
Parkinson’s disease (PD) is the most common neurodegenerative movement disorder, characterized by prominent degeneration of dopaminergic neurons in the substantia nigra and aggregation of the protein alpha-synuclein within intraneuronal inclusions known as Lewy bodies. Ninety percent of PD cases are idiopathic while the remaining 10% are associated with gene mutations that affect cellular functions ranging from kinase activity to mitochondrial quality control, hinting at a multifactorial disease process. Mutations in LRRK2 and SNCA (the gene coding for alpha-synuclein) cause monogenic forms of autosomal dominant PD, and polymorphisms in either gene are also associated with increased risk of idiopathic PD. Although Lewy bodies are a defining neuropathological feature of PD, an appreciable subset of patients with LRRK2 mutations present with a clinical phenotype indistinguishable from idiopathic PD but lack Lewy pathology at autopsy, suggesting that LRRK2-mediated PD may occur independently of alpha-synuclein aggregation. Here, we examine whether LRRK2 and alpha-synuclein, as mediators of neurodegeneration in PD, exist in common or distinct pathways. Specifically, we review evidence from preclinical models and human neuropathological studies examining interactions between the two proteins. Elucidating the degree of interplay between LRRK2 and alpha-synuclein will be necessary for treatment stratification once effective targeted disease-modifying therapies are developed.